The selenocysteine-inserting opal suppressor serine tRNA from E. coli is highly unusual in structure and modification. - Schön, A (1989)
Selenocysteine is cotranslationally incorporated into selenoproteins in a unique pathway involving tRNA mediated suppression of a UGA nonsense codon (1-3). The DNA sequence of the gene for this suppressor tRNA from Escherichia coli predicts unusual features of the gene product (4). We determined the sequence of this serine tRNA (tRNA(UCASer]. It is the longest tRNA (95 nt) known to date with an acceptor stem of 8 base pairs and lacks some of the 'invariant' nucleotides found in other tRNAs. It is the first E. coli tRNA that contains the hypermodified nucleotide i6A, adjacent to the UGA-recognizing anticodon UCA. The implications of the unusual structure and modification of this tRNA on recognition by seryl-tRNA synthetase, by tRNA modifying enzymes, and on codon recognition are discussed.